A numerical solution for non-classical parabolic problem based on Chebyshev spectral collocation method - Golbabai, A.; Javidi, M. (Applied mathematics and computation, 2007)
A numerical method based on Chebyshev polynomials and local interpolating functions is proposed for solving the one-dimensional parabolic partial differential equation subject to non-classical conditions. To assess its validity and accuracy, the method is applied to solve several test problem.